2022
DOI: 10.3390/nu14010211
|View full text |Cite
|
Sign up to set email alerts
|

Higher Iron Intake Is Independently Associated with Obesity in Younger Japanese Type-2 Diabetes Mellitus Patients

Abstract: We aimed to analyze the association between dietary iron intake and obesity assessed by BMI after adjustment for nutrient intake (macronutrients and fiber) and food groups. The study design was cross-sectional. Patients with type-2 diabetes (n = 1567; 63.1% males; mean age 62.3 ± 11.6 years) were included in the study. To assess diet, consumption of typical food groups was determined by a food frequency questionnaire. Obesity was defined as BMI ≥ 25 kg/m2. We performed a binary regression analysis between quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…A meta-analysis of fourteen observational studies indicated that the dietary iron level has significant positive association with MetS [ 61 ]. In a cross-sectional research of 1567 Japanese individuals with type-2 diabetes, Ferreira ED et al[ 62 ] found that regardless of macronutrient and fiber intake, participants in the highest quartile of iron intake had a significantly higher risk of obesity in the 30- to 54-year-old age group. Meanwhile, studies have shown that serum ferritin level has a positive correlation with WC, BMI [ 63 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of fourteen observational studies indicated that the dietary iron level has significant positive association with MetS [ 61 ]. In a cross-sectional research of 1567 Japanese individuals with type-2 diabetes, Ferreira ED et al[ 62 ] found that regardless of macronutrient and fiber intake, participants in the highest quartile of iron intake had a significantly higher risk of obesity in the 30- to 54-year-old age group. Meanwhile, studies have shown that serum ferritin level has a positive correlation with WC, BMI [ 63 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In excess, Fe promotes the formation of reactive oxygen species and consequent DNA damage and lipid peroxidation, which contribute to the development of type 2 diabetes (T2D), cancer, and cardiovascular diseases [62]. However, longitudinal studies have shown conflicting results regarding the association of Fe intake with the abovementioned conditions [63]. Meta-analyses have indicated an increased risk of disease due to excessive consumption of heme Fe alone, which may therefore be explained by excessive consumption of highfat meat and offal products [64][65][66][67].…”
Section: Effects Of Micronutrient Supplementation On Weight Managemen...mentioning
confidence: 99%